Improving Motivation in Social Sciences Subjects Using Powerpoint Media: Study at SMP Negeri 2 Karau Kuala - Saliman Saliman; Ahmad Effendi; Hanif Nur Rokhim; Satriyo Wibowo (Universitas Negeri Yogyakarta, 2026)
This study aims to improve students’ learning motivation in Social Studies through the use of PowerPoint media among ninth-grade students at SMP Negeri 2 Karau Kuala. The background of this research is the low learning motivation of students in Social Studies classes, which affects their participation and learning outcomes. Therefore, it is necessary to innovate the learning process by utilizing interactive digital media to make learning more engaging and meaningful. This research employed a Classroom Action Research (CAR) design conducted in three cycles, including planning, implementation, observation, and reflection stages. The subjects of this study were 32 students of class IX A at SMP Negeri 2 Karau Kuala in the 2025 academic year. Data were collected through observation, interviews, and documentation, while data analysis was carried out using descriptive qualitative methods focusing on ten aspects of learning motivation. The instrument validation results indicated that all items were valid and reliable for measuring students’ motivation levels. The results showed that the use of PowerPoint media significantly improved students’ learning motivation in each cycle. The percentage of students with high motivation increased from 6.3% in the pre-cycle to 16% in the first cycle, 25% in the second cycle, and 63% in the third cycle. The average motivation score also rose from the low category (16.9) in the pre-cycle to moderate (23.9) in the first cycle, high (28.3) in the second cycle, and very high (34.3) in the third cycle. Students became more active, enthusiastic, and participative during lessons. Therefore, PowerPoint media is proven to be effective in enhancing students’ motivation in Social Studies learning and in creating an engaging, interactive, and enjoyable classroom environment.